Quale federalismo per l'Italia di oggi? Atti della Giornata di Studi promossa dalla Facoltà di Scienze Politiche "Cesare Alfieri" Per i 150 anni dell'Unità d'Italia - Rogari, Sandro (Atti, 2013)
On the occasion of the 150th anniversary of the Italian National Unity, the Faculty of Political Science "Cesare Alfieri" promoted a series of lessons on an interdisciplinary system on crucial issues of Italy's unitary constitution. At the end of this cycle of readings, on 28 November 2011 the Faculty promoted a day of study on the theme "Which kind of federalism for today's Italy". To this end, scholars were invited to offer their contributes and reflections which, from a historical, constitutional, sociological, political and economic perspective, could help taking the stock of the crucial issue of the federal redefinition of the Italian state. A varied and complex picture emerged, where the different disciplinary perspectives make up an integrated, multifaceted but not contradictory mosaic of possible federalism, aimed at regenerating the institutions of the Republic and their relationship with citizens. The volume collects the results of that day of study and proposes them to the reading of students and scholars.